The ‘Realness’ Discourse of a Political Leader: A Komunikasi Berasa Perspective - BAMBANG SUKMA WIJAYA (Jurnal Studi Pemerintahan, 2016)
This article examines the communication style of the former Governor of Jakarta and presidential candidate during the 2014 Indonesian election, Joko Widodo (known as Jokowi), both as a discourse and communication model that affects trustworthiness and meaningfulness of the audiences toward the conveyed messages.This communication model is called Komunikasi Berasa [‘sensed-communication’ or ‘experientially-meaningful communication’], which synergises the delivery and verification of a message through audiences’ experience towards the meaning of the message. Using discursive and descriptive survey approaches, the author found out that Jokowi’s sensed-communication is not perceived solely on blusukan [impromptu visits], but also on the verbal messages of his political campaigns. Media texts display more sensed-rational and sensed-sensorial discourse, whilst people see sensed-relevance and sensed-beneficial as the prominent factors in the sensed-message that Jokowi sent. The results of this research could be used as a reference in implementing a strategy to get audiences’ trust through Komunikasi Berasa or sensed-communication.